Gestational weight gain and weight retention at postpartum 12th month - Zuhal Emlek Sert; Zeynep Daşıkan (Cukurova Medical Journal, 2021)
Purpose: This study aimed to determine gestational weight gain (GWG) according to the Institute of Medicine (IOM) 2009 guidelines and postpartum 12th month weight retention, and to investigate the factors affecting it. Materials and Methods: This is a descriptive cross-sectional study of 216 postpartum women at 12 month. Questionnaire was used to collect the research data.. Results: 64.8% of women have been determined except for the 2009 IOM guideline recommendations (44% excessive GWG), postpartum weight retention was identified in 69.5% of the women (27.8% having ≥5 kg; 41.7% between 0.5-5kg). Obesity ratio increased by 9.3% in postpartum women at 12 month when compared to pre-pregnancy. Excessive GWG were found in women whose pre-pregnancy body mass index was overweight and obese, had education for> 8 years, had a good income level, and a baby birth weight of ≥4000 grams and had a primipara. Postpartum 12 month weight retention rates were observed in women with excessive GWG, and in women whose physical activity perceptions were immobile, with breastfeeding periods of ≤6 months. Conclusion: Approximately half of the participating women had excessive GWG, while two-thirds had postpartum weight retention at 12th month. There was 9.3% increase in the rate of obesity between pre-pregnancy and 12 months postpartum in the participating women. Prenatal care provider (midwife-nurse, obstetrician, family doctor etc.) should make recommendations for GWG according to IOM guidelines and weight management counseling to prevent excessive GWG and postpartum weight retention.